Nonhydrodynamic Translational Diffusion of a Coarse-Grained Wormlike Polyelectrolyte Chain Confined in Nanochannels by Using Brownian Dynamics Simulations - Chun, Myung-Suk (KOREAN PHYSICAL SOC, 2008)
A coarse-grained model of semiflexible anionic polyelectrolyte xanthan is applied and its structure and dynamics are examined with Brownian dynamics (BD) simulations both in a bulk solution and under confinement between two parallel plates. The modeling is based on the nonlinear bead-spring discretization of a chain with additional long-range electrostatic and hydrodynamic interactions between pairs of beads. Neutral and negatively-charged glass surfaces are combined to make three kinds of slit channels with different charge characteristics as neutral-neutral, glass-glass and neutral-glass walls, where uniform conditions of the surface charge density are assumed. Simulation parameters are obtained from previously reported rheology data on the native and sonicated xanthan polysaccharides. The structural transition of the chain and its dependence on the Debye screening of the electrolyte solution are characterized. The wall charge effect is found to be significant as the ionic strength decreases, where a strongly-charged glass wall strengthens the effective confinement of xanthan. A nonmonotonic variation of chain size with changing slit width is also observed in the neutral slit. An asymmetrically-charged slit call induce xanthan migration toward a less repulsive wall and a narrow-down of the chain distribution across the channel, suggesting the usefulness of surface treatment of channel walls to manipulate polyelectrolytes. We need to point out that the scaling law developed for neutral polymers is limited for direct application to polyelectrolytes.
Keywords: INTRINSIC-VISCOSITY; MOLECULAR-DYNAMICS; POLYMER-SOLUTIONS; BEHAVIOR; DNA; MACROMOLECULES; STATISTICS; TRANSPORT; XANTHAN; MODEL